2005
DOI: 10.1111/j.1582-4934.2005.tb00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of scaffolding, signalling and contractile-filament proteins in human myometria: effects of pregnancy and labour

Abstract: Successful parturition requires the co‐ordination of numerous myometrial signalling events to allow for timely and efficient uterine contractions. Late pregnancy and labour onset in humans may be associated with changes in the expression of myometrial proteins implicated in such uterine contractile signal integration. Accordingly, in myometria from non‐pregnant women and pregnant women, not in labour or in labour, we examined the content of putative plasmalemmal scaffolding proteins (caveolin‐1 and ‐2) and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 37 publications
4
32
0
Order By: Relevance
“…In line with this proposal, we first confirmed our previous data indicating that human cultured myometrial cells expressed functional binding sites and respond to purified SP-A to induce stress fiber formation via a pathway involving Rho-kinase (11). In human myometrium, Rho-kinase inhibition has been associated with reduction of uterotonic-induced myometrial contractions (9,12,35). We confirmed that pharmacological inhibition of Rho-kinase resulted in a clear reduction of stress fiber formation induced by SP-A.…”
Section: Discussionsupporting
confidence: 78%
“…In line with this proposal, we first confirmed our previous data indicating that human cultured myometrial cells expressed functional binding sites and respond to purified SP-A to induce stress fiber formation via a pathway involving Rho-kinase (11). In human myometrium, Rho-kinase inhibition has been associated with reduction of uterotonic-induced myometrial contractions (9,12,35). We confirmed that pharmacological inhibition of Rho-kinase resulted in a clear reduction of stress fiber formation induced by SP-A.…”
Section: Discussionsupporting
confidence: 78%
“…Estrogens are steroid hormones with important functions in the regulation of specific sexual processes in females; they affect the myometrium at the end of the pregnancy by decreasing cellular membrane potential which increases the excitability of the uterus (Kurowicka et al, 2005;Riley et al, 2005) and then intervene in the initiation of labour during child birth. In addition, uterotrophic substances such as oxytocin, a neurohypophysial hormone, are frequently used to enhance myometrial contractile activity during labour (Lopez Bernal, 2003), and it is known that the physiological regulation of the oxytocin system is strongly steroid-dependent (Gimpl and Fahrenholz, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Whatever it may be, genomic studies constitute a necessary first step of orientation which should lead to a more elaborate hierarchical vision of the physiological mechanisms of gestation, in particular by establishing new links between the generic signaling pathways that are activated during normal or pathological gestation. Genomic studies also represent an indicative step that will need to be correlated with a systematic proteomic analysis of the myometrium (Riley et al 2005a, Riley et al 2005b. The latter will undoubtedly develop in the very near future.…”
Section: Future Strategies For Integrative Analysis Of Myometrial Funmentioning
confidence: 99%